Metode Pendidikan Anak dalam Islam Perspektif Abdullah Nashih ‘Ulwan dalam Kitab Tarbiyatul Aulad Fil Islam - Syafik Ubaidilla; Dianis Izzatul Yuanita (Indonesian Journal of Humanities and Social Sciences, 2021)
The current trend of education is more concerned with the intellectual aspects of students, thus giving birth to people who are good at science but tend to be lacking in morals, ethics and religious values. Seeing this fact, the author raises the method of educating children in Islam from a well-known Islamic figure and it is proven that his work has existed for a very long time and also from the Qur'an and Hadith. The method used is hermeneutic, namely using linguistic logic by making explanations and understandings of the meaning of words and the meaning of language as basic ingredients. The results of the study, the Abdullah Nashih 'Ulwan method is very suitable for making our students understand commendable morals, making our students able to distinguish bad qualities and our students have strong religious provisions in accordance with the teachings of the Qur'an and Assunnah. , and the methods of other scholars/figures can also be taken as a reference for educating our children. Exemplary methods, customs, advice, giving attention, giving punishment, lectures, stories, questions and answers, discussions and others. And also like the teaching method in the environment, according to him, is very influential in education. The environment in question is a family, community, educational institutions and mosques. According to him, educators and students must decorate themselves with sincere intentions, good qualities and noble character. Abdullah Nashih 'Ulwan's comprehensive educational method is still very relevant to the educational methods of other scholars and also to the current Modern Education Method.